Energy Analysis of a Diesel Engine Using Diesel and Biodiesel from Waste Cooking Oil - S Abbasi (Ferdowsi University of Mashhad, 2018)
Introduction The extensive use of diesel engines in agricultural activities and transportation, led to the emergence of serious challenges in providing and evaluating alternative fuels from different sources in addition to the chemical properties close to diesel fuel, including properties such as renewable, inexpensive and have fewer emissions. Biodiesel is one of the alternative fuels. Many studies have been carried out on the use of biodiesel in pure form or blended with diesel fuel about combustion, performance and emission parameters of engines. One of the parameters that have been less discussed is energy balance. In providing alternative fuels, biodiesel from waste cooking oil due to its low cost compared with biodiesel from plant oils, is the promising option. The properties of biodiesel and diesel fuels, in general, show many similarities, and therefore, biodiesel is rated as a realistic fuel as an alternative to diesel. The conversion of waste cooking oil into methyl esters through the transesterification process approximately reduces the molecular weight to one-third, reduces the viscosity by about one-seventh, reduces the flash point slightly and increases the volatility marginally, and reduces pour point considerably (Demirbas, 2009). In this study, effect of different percentages of biodiesel from waste cooking oil were investigated. Energy distribution study identify the energy losses ways in order to find the reduction solutions of them. Materials and Methods Renewable fuel used in this study consists of biodiesel produced from waste cooking oil by transesterification process (Table 1). Five diesel-biodiesel fuel blends with values of 0, 12, 22, 32 and 42 percent of biodiesel that are signs for B0, B12, B22, B32 and B42, respectively. The test engine was a diesel engine, single-cylinder, four-stroke, compression ignition and air‌cooled, series 3LD510 in the laboratory of renewable energies of agricultural faculty, Tarbiat Modarres University. The engine is connected to a dynamometer and after reaching steady state conditions data were obtained (Fig. 1). In thermal balance study, combustion process merely as a process intended to free up energy fuel and the first law of thermodynamics is used (Koochak et al., 2000). The energy contained in fuel converted to useful and losses energies by combustion. Useful energy measured by dynamometer as brake power and losses energy including exhaust emission, cooling system losses and uncontrollable energy losses. Variance analysis of all engine energy balance done by split plot design based on a completely randomized design and the means were compared with each other using Duncan test at 5% probability. Results and Discussion Results showed that, in general, biodiesel use has a significant impact on all components of energy balance. Of total energy from fuel combustion, the share of energy losses to form of exhaust emissions the maximum value in all percentages allocated to biodiesel (Average 51.715 percent) with the maximum and minimum amount of B42 (55.982 percent) and B0 (46.481 percent), respectively (Fig. 2). Also, fuel blend with 12% biodiesel was diagnosed the best blend because of having the most useful power, having the lowest energy losses through the exhaust and cooling system. Conclusions Using biodiesel produced from waste cooking oil by transesterification process, lead to increase the useful power. The addition of biodiesel to pure diesel cause to significant reduction in the waste energy due to friction. In higher amounts of biodiesel increase energy losses especially through the exhaust and cooling system due to higher viscosity.